The Effect of Realistic Mathematics Education Learning Model on Students’ Triarchic Intelligence - Michael Christian Simanullang (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
This study aims to analyze the effect of the Realistic Mathematics Education (RME) learning model on students' triarchic intelligence. This study is a quasi-experiment with a pretest-posttest control design. The instruments used in this study were: (1) validation sheets; and (2) students' triarchic intelligence tests. The results of this study are: (1) the students' triarchic intelligence scores taught with the RME learning model are in the high category; (2) there is a significant difference on the students' triarchic intelligence scores taught by the RME learning model and direct learning; (3) the students' triarchic intelligence scores taught by the RME learning model is higer than the students' triarchic intelligence scores taught by direct learning; and (4) the implementation of the RME learning model can increase students' triarchic intelligence.Keywords: Quasi-Experiment, Learning Model, RME, Triarchic Intelligence